The Spiritual Health of Seniors Living in Sanitarium and Home Residents - M Saydshohadai; Sh Heshmat; N Seidfatemi; H Haghani; N Mehrdad (Iran University of Medical Sciences, 2013)
Background & Aim : The phenomenon of the increasing number of old people population is one of the most important socio economic and health challenges in the 21st century. This challenge persuades the governors to consider more importance for these people's health and specially their spiritual health which is often neglected. Therefore the present study has been conducted to compare the spiritual health of seniors living in sanitarium and home residents.   Material & methods : It was a cross-sectional comparative study. The sample included 209 seniors living in sanitarium and home residents. The home residents were recruited by cluster sampling from health centers of south Tehran and the sanitarium residents were selected by convenience sampling. Data was collected using demographic sheet and Elison and Palotzin Questionnaire with two parts of religious and existential health and analyzed by T test and chi square test and ANOVA using SPSS-PC (v.18).   Results: The mean score of spiritual health of seniors living in sanitarium and home residents was 63.92±6.7 and 60.08±9.3 respectively. The dimensions of religious and existential health of spiritual health were significantly different between the two groups (p=0/001).   Conclusion: Regarding the findings of this study, considering the factors related to promotion of spiritual health of this group of society especially home residents is recommended in their care.   Received: 14 Apr 2013   Accepted: 25 Jun 2013